DESAIN DAN PEMBUATAN PROTOTIPE CARLSON SURGE DEVICE (CSD) UNTUK BUDIDAYA KARANG HIAS - Hakim, Muhammad Romdonul; Kusdinar, Afriana; Ahmadi, Haidar Atsil Meyshaffa; Firdaus, Anas Noor (Politeknik Kelautan dan Perikanan Sidoarjo, 2024)
As the interest in marine aquariums increases, so does the demand for ornamental corals. One of the parameters needed for coral growth is water flow. The Carlson Surge Device (CSD) is a tool that can generate water currents similar to natural sea currents found in coral reefs. This research aims to create a CSD that is easy and inexpensive to produce, so it can be widely applied in ornamental coral cultivation tanks by the community. By optimizing the cultivation of ornamental corals, it is hoped that the damage to coral reef ecosystems caused by illegal coral harvesting in nature can be minimized. This research uses an experimental method by testing PVC pipe diameters of 1 inch, 1.5 inches, 2 inches, and 2.5 inches. The CSD design created has reservoir dimensions with a diameter of 36 cm and a height of 35 cm, and uses PVC pipes with an inner pipe length of 20 cm and an outer pipe length of 44 cm. The results of this study show that the use of 2.5-inch diameter PVC pipes can produce a water flow rate of 0.28 m/s, which is suitable for coral growth, while the water flow produced by other pipe diameters is still too strong. These results indicate that the CSD prototype that has been made is suitable for application in ornamental coral cultivation tanks.